ANALISIS MINAT MENJADI GURU PADA MAHASISWA PENDIDIKAN EKONOMI ALUMNI PROGRAM KAMPUS MENGAJAR - Sapitri, Cella (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research was conducted with the aim of analyzing interest in becoming a teacher, which is a situation where a person has a strong desire to become a teacher, is happy in carrying out the teaching profession and is enthusiastic about the profession. Reviewed using a cognitive, affective and conative perspective on Economic Education students who are alumni of campus teaching programs. This research uses a qualitative approach method, with a case study type of research. The research informants were determined using the snowball sampling technique, totaling 7 people. The results of the research show that (1) the cognitive perspective of Economic Education students from teaching campus alumni can increase their interest in becoming teachers because by participating in the teaching campus program students are given the opportunity to go directly to the field so they can find out directly what is happening in the field and gain more knowledge. new about the teaching profession, (2) the affective perspective of Economic Education students from teaching campus alumni can increase their interest in becoming teachers because they feel happy in teaching students directly, so as is known, when you feel happy doing something you will definitely be interested in doing that thing, (3) conation perspective on Economic Education students, alumni of teaching campuses can increase their interest in becoming teachers because they have a high desire to teach so that they will consciously obey existing regulations in order to be responsible and self-disciplined.